Evaluation of performance and early degradation of a 180.8 KWP rooftop on a grid-connected photovoltaic system in a Colombian tropical region environment - Audivet, Cinthia; Romero, Elena; García, Jesús; Fonseca, Ana; Pinzón, Horacio; Bula, Antonio; Sanjuan, Marco (CT&F - Ciencia, Tecnología y Futuro, 2021)
The use of renewable energy such as photovoltaic is growing. According to IRENA, these systems are one of the most dynamic generation technologies. The global photovoltaic market has grown rapidly between 2000 and 2016 at an annual average compound rate of 44%, from 0.8 GW to 291 GW. In Colombia, regions with high solar irradiation levels have been identified as emerging markets. The Government's plan is to increase the share of non-conventional energies in the energy matrix from 2% to 8% - 10%. However, the uncertainties associated with technology and sites specific degradation rates make it difficult to calculate accurate electricity generation efficiencies and predicting future performance and material degradation rates, and thus business models exhibit considerable deviations related to the real electricity generation rates. This work studies the performance and early degradation of a 180.8 kWp rooftop on grid connected photovoltaic system, installed in Barranquilla, Colombia. Two methods were used: i) estimation of solar conversion efficiency, and ii) visual inspection. The first method includes a cross analysis of climatic conditions, irradiance levels, and the generated energy downstream the inverters. The second method consists of periodical visual inspections of installed modules to check: discoloration, delamination, busbar corrosion, cracking of solar cell, glass breakage, anti-reflection coating, and solder bond.